USING INSIDE DEMONSTRATION METHODS IMPROVING STUDENT UNDERSTANDING ABOUT THE SURFACE OF THE EARTH AND THE SKY OF TEACHING SCINCE - Dicky Hendarsyah; Anugrah Ramadhan Firdaus (COLLASE (Creative of Learning Students Elementary Education), 2018)
This study aims to improve student motivation, activity, and learning achievement in learning changes in the appearance of the earth's surface and celestial bodies using the Demonstration method. The use of the Demonstration method is expected to increase student activity in the teaching and learning process so that in the teaching and learning process there is no saturation in teaching and learning activities. Thus, students will be involved physically, emotionally, and intellectually which in turn is expected to change the concept of objects taught by the teacher to be understood by students. This study uses action research conducted in two cycles. Each cycle consists of four actions, namely planning, action, observation and reflection. The target of this research is students in grade IV SDN 024 Coblong, Coblong Subdistrict, Bandung City with 38 students. Data obtained in the form of formative test results and observation sheets of teaching and learning activities. From the results of research and analysis found that student achievement has increased from the first cycle of action 1, namely 78.4%, action 2: 88.2%, action 3: 95.35%, action 4: 98.25%. The behavior is 1, which is 95%, action 2: 97.20%, action 3: 98.08%, and action 4: 99.50%.